Research of ergatic system "airplane-crew-environment" reliability - Юрченко, О. І.; Готун, О. В. (Proceedings of National Aviation University, 2000)
By means of Markovian process of randomness and differential equations formulated is mathematical model of aircraft operation as a constituent part of ergatic system "airplane-crew- environment"